2020
DOI: 10.1186/s40168-020-0788-1
|View full text |Cite
|
Sign up to set email alerts
|

Gastric bypass surgery in a rat model alters the community structure and functional composition of the intestinal microbiota independently of weight loss

Abstract: Background: Roux-en-Y gastric bypass (RYGB) surgery is a last-resort treatment to induce substantial and sustained weight loss in cases of severe obesity. This anatomical rearrangement affects the intestinal microbiota, but so far, little information is available on how it interferes with microbial functionality and microbial-host interactions independently of weight loss. Methods: A rat model was employed where the RYGB-surgery cohort is compared to sham-operated controls which were kept at a matched body wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 89 publications
(104 reference statements)
6
47
0
Order By: Relevance
“…However, previous findings from diet-induced obese mice and rats, as well as genetically obese and insulin-resistant ZDF rats, have established that reduced intestinal permeability/attenuated endotoxemia following RYGB occur independently of food/high-fat diet restriction and weight loss ( Guo et al., 2019 ; Steensels et al., 2017 ; Wang et al., 2019a ). Additionally, we previously found that colonic CA and CDCA concentrations are twice as high in RYGB-operated, diet-induced obese rats compared with body weight-matched, sham-operated counterparts ( Haange et al., 2020 ), further supporting the view that gastrointestinal reconfiguration-induced changes in bile flow and bile acid metabolizing intestinal microbiota per se , contribute to increased colonic FXR activation and stabilization of the IEB ( Figure 6 ). This is also supported by the finding that the jejunal contents of RYGB-operated rats stabilized barrier function in Caco-2 cells independently of FXR, since bile flow is redirected away from the upper/mid jejunum post-operatively.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…However, previous findings from diet-induced obese mice and rats, as well as genetically obese and insulin-resistant ZDF rats, have established that reduced intestinal permeability/attenuated endotoxemia following RYGB occur independently of food/high-fat diet restriction and weight loss ( Guo et al., 2019 ; Steensels et al., 2017 ; Wang et al., 2019a ). Additionally, we previously found that colonic CA and CDCA concentrations are twice as high in RYGB-operated, diet-induced obese rats compared with body weight-matched, sham-operated counterparts ( Haange et al., 2020 ), further supporting the view that gastrointestinal reconfiguration-induced changes in bile flow and bile acid metabolizing intestinal microbiota per se , contribute to increased colonic FXR activation and stabilization of the IEB ( Figure 6 ). This is also supported by the finding that the jejunal contents of RYGB-operated rats stabilized barrier function in Caco-2 cells independently of FXR, since bile flow is redirected away from the upper/mid jejunum post-operatively.…”
Section: Discussionsupporting
confidence: 60%
“…This revealed region-specific, barrier-stabilizing effects for the intestinal contents of RYGB-operated compared with sham-operated rats, possibly mediated by the action of various host- and/or microbiota-generated soluble factors. These potentially include, but are not limited to, hepatocyte-derived conjugated primary bile acids, that may become concentrated in the duodenum following RYGB due to redirection of ingested food passage to the mid-jejunum ( Ise et al., 2019 ), as well as microbiota-derived metabolites such as indole-3-propionic acid ( Jennis et al., 2018 ; Natividad et al., 2018 ), secondary bile acids ( Haange et al., 2020 ; Lajczak-McGinley et al., 2020 ), taurine ( Ahmadi et al., 2020 ; Wang et al., 2019a ), and the short chain fatty acid propionate ( Liou et al., 2013 ; Tong et al., 2016 ). Future metabolomics studies are required to confirm this, and to potentially discover novel soluble factors that stabilize the IEB.…”
Section: Discussionmentioning
confidence: 99%
“…For this purpose, mouse models, using calorie restriction or sham-operated pair-fed individuals as diet-matched controls could be a helpful tool. There is some evidence from experimental studies on rats, which indicates that the observed effects on gut microbiota composition and diversity after RYGB surgery are associated with surgery itself [84,85]. Guo et al found similar glucose improvement and increased gut microbiota diversity 10 weeks after RYGB and SG surgery compared with the sham-operated groups (pair-fed as RYGB or fed ad litidum).…”
Section: Impact Of Gastric Bypass Surgery On Gut Microbiotamentioning
confidence: 99%
“…[ 55 , 57 ] Many studies reported that intestinal rearrangement after RYGB is a vital factor for the gut microbial changes. [ 59 , 60 , 64 ] Nevertheless, proton pump inhibitor therapy during the first 3 months after surgery and antibiotics used during the peri-operative period can also influence the gut microbiota, which clinicians should be aware of. Does the changed gut microbiota have some effects on metabolic alterations after RYGB?…”
Section: The Gut Microbiota Is Significantly Altered After Rygbmentioning
confidence: 99%